How inflammation impinges on NAFLD: A role for Kupffer cells - Duarte, Nádia (2017)
This study was supported by Fundacao para a Ciencia e Tecnologia (FCT) Grants PTDC/DTP-EPI/0207/2012 and PTDC/BIM-MET/0486/2012 and by the Portuguese Diabetes Society (SPD).